DO REMITTANCES “MAKE IT” FOR THEIR MEMBERS LEFT BEHIND? URBAN TO RURAL REMITTANCES BY MIGRANTS IN FOUR INDONESIAN CITIES - Tadjuddin Noer Effendi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2015)
This paper examines the nature, extent, and effect of remittances sent by urban migrants to home villages. More specifi cally it examines: the magnitude of remittances, type and background of migrants sending remittance, the extent of remittances sent, and the use of remittances. This study is carried out in four major cities in Indonesia that have experienced signifi cant infl ows of rural–urban migrants over the past few decades: Tangerang in Banten, Samarinda in East Kalimantan, Medan in North Sumatra and Makassar in South Sulawesi. Using survey data collected in 2008-2009, this study found that, over time, rural-urban migrants have an opportunity to save portion of their income that subsequently send the remittances out to home village. Rural-urban migrants seem need time to be older and reach a certain level of income before they begin to send remittance. Statistically, age is among personal backgrounds that have signifi cant effect on propensity to send or not send remittances. One of important social dimensions of rural-urban migration in many developing countries is its effect on household members, particularly household members or children left behind. This does not seem to be the case in four cities under study, where many urban-rural migrants are accompanied by their members (wives and children).